2022
DOI: 10.1093/tropej/fmac055
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Xpert MTB/RIF in the Diagnosis of Childhood Tuberculosis in Rural Ethiopia

Abstract: Background This study assesses the impact of the Xpert MTB/RIF in the diagnosis of childhood tuberculosis (TB) in a rural hospital in a resource-constrained setting. Methods Retrospective cross-sectional study in children evaluated for presumptive TB from 1 June 2016 to 31 May 2017 at the Gambo General Hospital in rural Southern Ethiopia. Children were evaluated according to a defined protocol based on national guidelines. Sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Time to death: It was determined as the interval between the date of a clear MDR-TB diagnosis and the date of death (in months) [24] .…”
Section: Methodsmentioning
confidence: 99%
“…Time to death: It was determined as the interval between the date of a clear MDR-TB diagnosis and the date of death (in months) [24] .…”
Section: Methodsmentioning
confidence: 99%
“…GeneXpert MTB/RIF ® has been used as the primary tool for TB diagnosis in Ethiopia since 2015 [5]. Xpert is a more sensitive and specific test than microscopy, allowing for more accurate data generation to describe childhood TB epidemiology [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies done in Ethiopia reported the prevalence, impact, and molecular epidemiology dynamics of childhood TB [13][14][15][16][17][18][19][20]. However, information is scarce about the potential role and contributions of implementing alternative clinical, radiological, and microbiological TB diagnostic platforms for childhood TB case ndings.…”
Section: Introductionmentioning
confidence: 99%